2003
DOI: 10.1159/000074064
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance following Midtrimester Termination of Pregnancy

Abstract: The aim of the study was to determine the impact of midtrimester abortion with extra-amniotic PGE2 on future fertility and reproduction. Two hundred and fifteen women were enrolled. The mean induction-to-abortion interval was 21.3 h. The complication rate was 11.7%. Twenty women (9.3%) were lost to follow-up, 82 patients (38.1%) used contraception. Spontaneous pregnancy occurred in 110 out of 113 women who desired fertility (97%). Three patients were defined as infertile but conceived following trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…(23,24). A relatively high rate of terminations in our subfertile population thus tends to suggest that these women were able to conceive in the past and could favor an association of subfertility with increased age.…”
Section: Figurementioning
confidence: 79%
“…(23,24). A relatively high rate of terminations in our subfertile population thus tends to suggest that these women were able to conceive in the past and could favor an association of subfertility with increased age.…”
Section: Figurementioning
confidence: 79%
“…This could be due to the increased risk of acquiring pelvic infection with age (Bewley et al, 2005) or the effect of previous salphingectomy due to ectopic pregnancy. Earlier research has shown that previous terminations per se are not associated with impaired fertility in later life (Lurie et al, 1994;Debby et al, 2003).…”
Section: Ovulatory Dysfunction Versus Unexplained Infertilitymentioning
confidence: 96%
“…Rates vary between 0.77% and 8% for early infection (before day 7) and between 0.3% and 7.9% for late infection (after 8 days). 56,57 However TOP with extra-amniotic PGE2 may be associated with an increased rate of premature births in the next pregnancy. 46 Some complications may influence fertility and the course of subsequent pregnancies, such as uterine rupture, intra-uterine adhesions, pelvic inflammatory disease, or cervical incompetence.…”
Section: Morbiditymentioning
confidence: 99%